The association of advanced lung cancer inflammation index with non-alcoholic fatty liver disease in NHANES 2017–2020 - Cheng, Lin; Li, Shumeng; Li, Hui; You, Jiafeng; Yu, Mingwei; Yang, Guowang (Frontiers in Medicine, 2025)
BackgroundThe advanced lung cancer inflammation index (ALI) is a composite index that combines inflammation and nutritional status, and non-alcoholic fatty liver disease (NAFLD) is associated with inflammation, nutritional status, and obesity. This study aimed to investigate the possible relationship between ALI and NAFLD.MethodsWe extracted cohort datasets from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) for the study. Weighted analyses and multivariate linear regression models were applied to assess the association between ALI and NAFLD. Fitted curves and threshold effects analyses were used to characterize nonlinear relationships.ResultsA total of 6,595 adults aged 18–80 years were included in this study. In multivariate linear regression analysis, there was a significant positive association between ALI and NAFLD [OR: 1.02, 95% CI (1.01, 1.02)]. In subgroup analyses, this positive association was maintained in females [OR: 1.02, 95% CI (1.01, 1.02)] and not in males. In addition, we found that the association between ALI and NAFLD was nonlinear, with an L-shaped relationship and an inflection point of 32.47. ALI showed a U-shaped association with NAFLD in the male population, with an inflection point of 40.65, and an L-shaped association in the female population, with an inflection point of 30.61.ConclusionOur study suggests that there is a significant positive association between high ALI levels and NAFLD prevalence in the US adult population. However, more clinical cohort studies are needed to confirm this finding.